Pengaruh Media Kantong Kangguru Terhadap Hasil Belajar Matematika Siswa Kelas II SDN 105345 Sidodadi Ramunia Tahun Ajaran 2023/2024 - Rita Budiarti; Emy Hariati; Leni Malinda (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
This study aims to determine the influence of kangaroo pouch media usage on mathematics learning outcomes in second-grade students of SDN 105345 Sidodadi Ramunia in the academic year 2023/2024. The subject matter is place value. This research is motivated by the mathematics learning outcomes of students that are still below the Minimum Completeness Criteria (KKM).This study is a True Experimental Type Non-Equivalent Control Group Design. It involves two groups: the experimental group, which receives treatment using kangaroo pouch media, and the control group, which undergoes lecture-based learning. The variables in this research consist of the independent variable, which is the kangaroo pouch media, and the dependent variable, which is the mathematics learning outcomes regarding the subject matter of place value. This is a population study with a population size of 36 students. The sample consists of 18 students, which form the experimental group. The instrument used in this study is a test questionnaire. Data analysis technique employed in this research is the t-test.The results of this study indicate that there is an influence of kangaroo pouch media usage on mathematics learning outcomes regarding the subject matter of place value in second-grade students of SDN 105345 Sidodadi Ramunia. This is evidenced by the t-test calculation results, which show a difference between the post-test scores of the experimental group and the control group. Based on the paired sample t-test calculation results, the significance value (2-tailed) is 0.001. In line with the hypothesis decision-making criterion that the significance value (2-tailed) < 0.05 or 0.001 < 0.05, it can be concluded that H0 is rejected and H1 is accepted because there is a significant difference between pretest and post-test results. Thus, the usage of kangaroo pouch media significantly influences the mathematics learning outcomes regarding the subject matter of place value for second-grade students of SDN 105345 Sidodadi Ramunia.